Exploring the use of online social networking among employees in Malaysian organizations: looking potential threats to information security - Abdul Molok , Nurul Nuha (s.n, 2013)
The proliferation of online social networking (OSN) sites such as facebook Linkedln, myspace and twitter by employees has posed threats to organizational information security. The western literature often report incidents of OSN causing malware attacks on corporate networks, leakage of confidential information, identity theft, cyber espionage and sabotage. Thus, this study investigates the use of OSN sites among employees of Malaysia organization including academic and non-academic staff of IIUM